Investing Amid Turmoil: Diversification Opportunities in Islamic Stock Indices, Bitcoin, Gold, and Crude Oil - Ahmad Monir Abdullah; Maizatulakma Abdullah; Romlah Jaafar; Noradiva Hamzah; Hishamuddin Abdul Wahab (Penerbit UKM, 2024)
Indexed by Scopus/MyCite